KORELASI ANTARA INTENSITAS PENGGUNAAN MEDIA SOSIAL DENGAN PERILAKU PROSOSIAL DI KALANGAN MAHASISWA (SUKMA : Jurnal Penelitian Psikologi, 2020)
This study aims to determine the correlation between the intensity of the use of social media with prosocial behavior among college students. The hypothesis proposed in this study is negative correlation between the intensity of the use of social media with prosocial behavior among collge students. The approach used in this research is a quantitative approach with correlational techniques. The subjects of this study were the 2016 psychology faculty students at the University of 17 Agustus 1945 Surabaya. The sample of this study amounted to 123 college students obtained through simple random sampling technique. Retrieval of research data using a scale of the use of social media intensity (24 valid items, ? = 0.913) and prosocial behavior scale (44 valid items, ? = 0.921). The data obtained in this study were analyzed using Product Moment Pearson correlation analysis to see the colleration between the intensity variables of social media use and prosocial behavior variables. The results of this study indicate that there is no correlation between the intensity of the use of social media with prosocial behavior, so the hypotheses proposed in this study were rejected. The intensity of the use of social media has a determination value of 0.013 which contributes an effective contribution og 1.3% while the remaining 98.7% is contributed by other factors not discussed in this study.Keyword : College students, intensity, prosocial behavior